(3GdbGfhf GdOSJhQj hGdfXe GdSjGSjI (B:s (3OQGSI ebGQfI HGdeHGOF GdOSJhQjI aj GdTQjYI GdESdGejI (B/s - (3GdeSdeGfj, eMeO CMeO EHQGgjes ((3GdEScfOQjI, eUQ (B:s (3OGQ GdacQ GdLGeYj,s, 2015)
(3jJfGhd cJGH (B((3GdbGfhf GdOSJhQj hGdfXe GdSjGSjI (B: (3OQGSI ebGQfI HGdeHGOF GdOSJhQjI aj GdTQjYI GdESdGejI(B) (3hGdPj bGe HJCdjag (B((3eMeO CMeO EHQGgje GdeSdeGfj(B) (3aj MhGdj (B(644) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdbGfhf GdOSJhQj(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdbSe GdChd (B: (3GdbGfhf GdOSJhQj ebGQfG HGdeHGOF GdOSJhQjI aj GdTQjYI GdESdGejI, GdHGH GdChd (B: (3JYQja GdbGfhf GdOSJhQj hYdGbJg HaQhY GdbGfhf GdCNQi, eUGOQ GdbGfhf GdOSJhQj aj GdfXe GdeYGUQI hGdacQ GdSjGSj GdESdGej, GdbSe GdKGfj (B: (3GdfXe GdSjGSjI, GdHGH GdChd (B: (3GdfXQjI GdYGeI ddOhdI, GdHGH GdKGfj (B: (3GdMcheI, GdHGH GdKGdK (B: (3JhRjY GdSdWGJ aj GdfXGe GdSjGSj GdhGMO(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdbGfhf GdOSJhQjs -- (3eUQs; (3GdfXe GdSjGSjIs -- (3eUQs; (3GdESdGe hGdbGfhf GdOSJhQjs